Pelatihan Praktikum IPAS pada Materi Sifat-Sifat Cahaya Kelas V SD Al-Ihsan Yapis Kotaraja - Kelana, Ardian Hangga; Irawan, Sakka; Suwarningsih, Tri; Suryani, Sri Woro; Tawil, Muh. (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
The purpose of this Community Service (PKM) activity is to provide science practical training on the material of light properties for grade V of SD Al Ihsan Yapis Kotaraja. Practical work is a learning process in the form of observation through experiments that aims to equip students to quickly understand theory and practice. Science learning should not only be given through theory, but also apply practical methods so that students can easily understand the concept of the material. This is in line with the development of the era and technology and the demands of 21st century learning that must be possessed by students, one of which is critical thinking skills. Practical methods can be applied to science subjects because students' skills are through the science process. This community service activity uses lecture, question and answer, discussion, and practical methods. Based on the results of direct observation and evaluation, the science practical training carried out by the PKM Lecturer Team has a positive impact on students, including; 1) Students are skilled in using simple science practical tools; 2) Increase the attitude of mutual cooperation when doing practical work; 3) Have a confident attitude through presentation of practical results.